The Influence of Organizational Culture, Work Environment, and Job Promotion on Work Motivation and Employee Performance - Sunyoto Sunyoto; Nanta Sigit (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Driven by the inconsistent achievement of performance targets among civil servants, this study investigates the critical determinants of work motivation and professional output within the public sector. Employing a quantitative explanatory research design, the analysis utilized data gathered from 142 purposefully selected civil officials through an online survey. The structural relationships were evaluated using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to ensure robust statistical inference. The empirical results indicate that organizational culture, the physical and social work environment, and job promotion opportunities exert positive and statistically significant effects on both employee motivation and overall performance. The work environment emerged as the most influential factor in driving these improvements. These findings suggest that public sector institutions should prioritize the cultivation of a cohesive culture, the optimization of workplace conditions, and the establishment of transparent, merit-based promotion frameworks. The research concludes that strategic organizational and managerial interventions are fundamental to enhancing the quality of human resources. By addressing these structural elements, public administration can effectively bridge the gap between current performance fluctuations and established institutional objectives, ensuring a more motivated and productive workforce in the long term.